The effect of prophylactic FVIII infusion combined with personalized rehabilitation on joint health and quality of life in children with hemophilia - Sun, Yaojin; Zhang, Qian; Gu, Xiaojie; Fang, Yongjun; Huang, Jie; Zhang, Heng (Frontiers in Pediatrics, 2025)
BackgroundHemophilia, a genetic disorder characterized by deficiencies in clotting factors VIII or IX, often results in joint and muscle bleeding, leading to hemophilic arthropathy and reduced quality of life. While multidisciplinary teams (MDTs) are widely used in hemophilia management, personalized rehabilitation strategies for pediatric patients remain underexplored. This study aimed to evaluate a 12-week individualized rehabilitation program targeting joint health in pediatric hemophilia patients.MethodsThis prospective study enrolled 59 children with hemophilia, implementing tailored rehabilitation plans based on specific joint pathologies. Assessments before and after treatment included joint ultrasound examinations (HEAD-US-C), Hemophilia Joint Health Scores (HJHS 2.1), and the CHO-KLAT tool for quality of life. Bleeding frequency was also recorded.ResultsPost-treatment, median HEAD-US-C scores decreased from 5.00 to 1.00 (P < 0.001), and HJHS 2.1 scores decreased from 9.00 to 2.00 (P < 0.001). CHO-KLAT scores increased from 71.51 to 79.15 (P < 0.001). Median bleeding episodes dropped from 3.00 to 0.00 (P < 0.001), indicating enhanced joint health and reduced bleeding frequency.ConclusionRegular prophylactic FVIII administration combined with individualized rehabilitation significantly reduces joint bleeding and enhances joint function and quality of life in children with hemophilia. The MDT approach is integral to comprehensive care, but further studies are needed to assess the long-term efficacy and safety of this therapeutic strategy.